Competition and Career Advancement - Julian Johnsen; Hyejin Ku; Kjell G. Salvanes (Center for Economic Studies and ifo Institute (CESifo), 2023)
In standard promotion tournaments, contestants are ranked based on their output or productivity. We argue that workers' career progression may also depend on their relative rankings in dimensions a priori unrelated to their job performance, such as visibility or in-person presence. Such implicit tournaments may rationalize a variety of seemingly counterproductive practices in the workplace, including long working hours, low uptake of statutory leave, and presenteeism. We illustrate the significance of implicit tournaments using the case of paternity leave among new fathers, where we exogenously vary a focal worker's ranking within a contest, not via his own leave status but that of his competitors, exploiting a policy reform. We show that the focal worker is put on a better earnings trajectory than otherwise when a larger share of his competitors take leave because of the reform. The focal worker's own absolute leave, however, has no direct effect on his earnings path as long as his own and his competitors' leave statuses are symmetric. With effective coordination, it should thus be possible for all fathers to utilize paternity leave without incurring unwarranted career costs. This has implications for statutory leave policies, flexible work arrangements, and gender equality.
Keywords: M51; M52; J16; J22; J24; J31; 330; implicit tournaments; relative rank; promotion; parental leave; flexible work arrangements; gender differences